Functions of Teachers' Narratives in EFL Classroom Contexts - Vahid Rahmani Doqaruni (Universidad Nacional de Colombia, 2023)
Although narratives have been widely used and investigated in the second/foreign language literature, studying narratives in authentic classroom contexts and their functions has received comparatively little attention. To fill this gap, the present study examines the narratives produced naturally by teachers within English-as-a-foreign-language classroom contexts to find out what functions these narratives serve. The participants were five Iranian teachers teaching general English courses in a private language institute. Following the principles of qualitative research in data analysis, 30 hours of naturally occurring data were first transcribed, then their narratives were identified. After analyzing the 23 determined narratives in the dataset, three functions of narratives emerged, namely, moral, pedagogical, and intercultural.